Tuning the selectivity toward CO evolution in the photocatalytic conversion of CO2 with H2O through the modification of Ag-loaded Ga2O3 with a ZnGa2O4 layer. Issue 4 (27th October 2015) - Wang, Zheng; Teramura, Kentaro; Huang, Zeai; Hosokawa, Saburo; Sakata, Yoshihisa; Tanaka, Tsunehiro
Abstract : Modification of Ag-loaded Ga2 O3 with a ZnGa2 O4 layer is effective for the highly selective photocatalytic conversion of CO2 by H2 O. Abstract : Stoichiometric evolutions of CO, H2, and O2 were achieved for the photocatalytic conversion of CO2 with H2 O as an electron donor using Ag-loaded Zn-modified Ga2 O3 . The selectivity toward the evolution of CO over H2 can be controlled by varying the amount of Zn species added in the Ag-loaded Zn-modified Ga2 O3 photocatalyst. The production of H2 gradually decreased with increasing amounts of Zn species from 0.1 to 10.0 mol%, whereas the evolution of CO was almost unchanged. The XRD, XAFS, and XPS measurements revealed that a ZnGa2 O4 layer was generated on the surface of Ga2 O3 by modification with Zn species. The formation of the ZnGa2 O4 layer eliminated the proton reduction sites on Ga2 O3, although the crystallinity, surface area, and morphology of Ga2 O3 as well as the particle size and chemical state of Ag did not change. In conclusion, we designed a highly selective photocatalyst for the conversion of CO2 with H2 O as an electron donor using Ag (the cocatalyst for the CO evolution), ZnGa2 O4 (the inhibitor of the H2 production), and Ga2 O3 (the photocatalyst).